Strategies in Vocabulary Learning : A Comparative Study on the Use of Learning Strategies between Lower and Upper Secondary School Students - Teittinen, Anniina (My University, 2019)
The topic of this thesis is vocabulary learning strategies in English. Vocabulary is a central area on the field of second language acquisition as language competence is largely built on the knowledge of words. The aims of the study were to investigate what kinds of vocabulary learning strategies learners use, what kinds of differences there are in the strategy use between the study groups and what kind of a relationship there is between strategy use and vocabulary proficiency. The goal was to gain knowledge on the use of vocabulary learning strategies and how this knowledge could be used in the educational context. This empirical study was conducted in Finland Proper and the study groups investigated were lower secondary school students and upper secondary school students. A vocabulary strategy taxonomy by Norbert Schmitt (1997) was used as the theoretical background for the study due to its adequate and diverse strategy classification. A vocabulary strategy questionnaire was used to measure strategy use and a vocabulary test measured vocabulary proficiency. The study was based on the quantitative research approach but the qualitative approach was also used in open-ended questions. The results implied that there are no significant differences in the strategy use between the groups. Upper secondary school students used on average more determination and social strategies. Lower secondary school students used more memory, cognitive and metacognitive strategies. The results were surprising as upper secondary school students were assumed to use more cognitive and metacognitive strategies due to their older age and more instruction in English referring to higher cognitive capacity. However, upper secondary school students used on average more vocabulary strategies. The relationship between strategy use and vocabulary proficiency showed negative correlation implying that the more one uses strategies, the worse vocabulary proficiency one has. Vocabulary learning strategies could therefore be understood as compensation strategies and strategies may also be used inappropriately. Vocabulary strategies should be integrated in the L2 instruction and teachers should support students to use strategies. Future research could concentrate on the effect of learning strategies by conducting more qualitative research.
Keywords: learning strategies, vocabulary, second language, acquisition, proficiency